2014
DOI: 10.4314/jab.v77i0.4
|View full text |Cite
|
Sign up to set email alerts
|

Effets de doses croissantes des composts de fumiers de poules sur le rendement de chou de Chine (<i>Brassica chinensis</i> L.) installé sur un sol acide de Lubumbashi

Abstract: Effects of increasing doses of compost on the performance of Chinese cabbage (Brassica chinensis L.) installed on an acid soil of Lubumbashi Objective: A study was conducted on a ferralsol to assess the agronomic efficiency of manure from chickens and mineral fertilizers (NPK and urea) on the yield of Chinese cabbage. Methodology and Results: The experimental design was a completely randomized with six repetitions and six treatments: T0 (unfertilized control), T1 (175 kg NPK +87 kg urea per hectare), T2 (350 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The most robust subjects (12.66 mm) were obtained from the T3 treatment where there was a mixture of both residues compared the control (9.00 mm). This higher response is for sure related to the combined action of improving soil properties and mineralized nutrients as reported in the literature [15]. The ANOVA showed that the coefficient of variation remains below 50% i.e.…”
Section: The Diameter Of the Collarsupporting
confidence: 73%
See 4 more Smart Citations
“…The most robust subjects (12.66 mm) were obtained from the T3 treatment where there was a mixture of both residues compared the control (9.00 mm). This higher response is for sure related to the combined action of improving soil properties and mineralized nutrients as reported in the literature [15]. The ANOVA showed that the coefficient of variation remains below 50% i.e.…”
Section: The Diameter Of the Collarsupporting
confidence: 73%
“…This means that compost as a valuable organic material is the source of minerals responsible for the growth including nitrogen [14]. It emerges that the evolution of growth was side by side at the beginning of the vegetation and grew in size at the third week because during this period the radicular apparatus became powerful to fulfill its physiological function by emitting nurturing roots for good growth [15]. This growth is stimulated by the synergistic combination of compost based on the mixture of groundnut and maize crop residues because of their enrichment in nitrogen and phosphorus [16].…”
Section: Figure 2 Weekly Evolution Of Plant Growth (Cm) In Relation To Compostsmentioning
confidence: 99%
See 3 more Smart Citations